On Refinements of Aczél, Popoviciu, Bellman's Inequalities and Related Results - Farid G; Pečarić J; Rehman AtiqUr (Journal of Inequalities and Applications, 2010)
We give some refinements of the inequalities of Aczél, Popoviciu, and Bellman. Also, we give some results related to power sums.